Radio Błyskawica (Lightning) during the Warsaw Uprising and its Meaning in the Memories of its Creators and Listeners. Issue 1 (2nd January 2022) - Wróbel, Wioleta; Doliwa, Urszula
Abstract : Radio 'Błyskawica', broadcasting during the Warsaw Uprising from the capital city of Poland, was the Second World War phenomenon - it was the only case during the war that from the occupied country a regular programme was broadcast. In the present article we try to show its activity from the human perspective, taking into consideration those who had a chance to broadcast but also listen to the station. Based on the personal testimonies gathered directly from around 95 witnesses of the Warsaw Uprising and indirectly via around 100 press articles published after the Second World War about this radio station, we describe the understanding of the mission of the station as well as the meaning of the station for the creators and the Warsaw insurgents.